From Political Decline to a Holy Revolt: Historical Comparison Between The Java War and Mahdist War - Khalisa, Fathia Alma; Zahra, Aliyandra Atthia; Nourabiaz, Nayla Rahdaulia; Adam, Yusril Fahmi; Ardi, Syafiya Mulyo (NALAR, 2025)
This study aims to compare the Java War and the Mahdi War as 19th-century holy revolts. This article contributes to an alternative history of the Java War, with the central figure being Prince Diponegoro, and, at the same time, places it in a global colonial context and connects it to the Mahdist War in Sudan. In its analysis, this study uses historical methods, political approaches, and conflict theory. The analysis in this study shows that the outbreak of the Java and the Mahdist War positioned Islam as the driving force behind the resistance, which was primarily caused by the political degradation of colonialism that gripped Java and Sudan. In this context, the combatants in the Java and Mahdist wars believed that their fight was a form of jihad (holy war). In the context of historiography, this article contributes to broadening the reading of colonial war history by placing Islam as an important basis for legitimacy and mobilization in the anti-colonial struggle.